PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI ASSEMBLR PADA MATERI STRUKTUR BUMI BERBASIS TEKNOLOGI 3 DIMENSI PADA MATA PELAJARAN IPAS DI KELAS V - Aprianti, Dwi; Andriana, Encep; Syachruroji, A. (Jurnal Pendidikan : Riset dan Konseptual, 2025)
Well-designed learning media can be used as a powerful tool to stimulate students' interest in learning and improve their understanding of the subject matter. The purpose of this study is to determine the development, feasibility, student responses and effectiveness of the assembly application learning media. The research method used is Research and Development (R&D) through the utilization of the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The data examination and validity technique uses expert feasibility testing, product trials (student responses), and media effectiveness testing using normalized gain testing which is carried out by working on pretests and posttests. The expert feasibility test obtained a final result of 90.77% with a very feasible category. The product trial by looking at student responses obtained a final result of 88% with a very good category. The media effectiveness test was measured by n-gain carried out through pretests and posttests, obtaining a final result of 78% which was stated in the effective category. Therefore, the study shows that the use of the assembler application significantly improves the quality of learning of earth structure material for fifth grade students. This media has proven effective in helping students achieve a deeper understanding of concepts.